HR analytics and innovations in workforce planning - Miller, Tony (Management consultant) (Human resource management and organizational behavior collection., 2017)
This book sets out new approaches, formulas, and software needed to enable any HR function or organization to forecast trends and to use existing retrospective data to their organization's advantage; which, in short, is to maximize efficiency and productivity. You will encounter the new formulas to use and new approaches that will add value. You will find out that most of the existing 52 formulas available don't work in today's environment. There is new software that will enable you to do forecasts with certainty and you can use a new mathematical model to rightsize any organization. Are you using an outdated organizational model? Do you have processes that don't work any more? These are areas which are major inhibitors to productivity and can be significantly improved. Most important of all is that this book will help you to create immense added value in any organization.